Opportunities in journalism - Tebbel, John William, 1912- (Louisville, Ky: Vocational Guidance Manuals, 1977)
Discusses the field of newspaper journalism including its history, various jobs, career opportunities, and educational requirements.
Includes index.
Bibliography: p. 135-136.
Keywords: Journalism -- Vocational guidance